Современные электромобили – тенденции развития в Украине - Басс, К. М.; Кривда, В. В.; Пасичник, Е. А. (Видавництво НГУ, 2018)
В работе анализируются достоинства и недостатки электрокаров, а также их внедрение и применение в Украине и Европе.

The advantages and disadvantages of electric cars, as well as their introduction and application in Ukraine and Europe are analyzed.
Actual electric vehicles development trends in Ukraine
Keywords: электромобиль; electric car; электрокар; electric trolley; зарядные станции; charging stations; электрический транспорт; electric transport